Reducing Vulnerability to Climate Change in the Arctic: The Case of Nunavut, Canada - Ford, James; Pearce, Tristan; Smit, Barry; Wandel, Johanna; Allurut, Mishak; Shappa, Kik; Ittusujurat, Harry; Qrunnut, Kevin (ARCTIC, 2009)
Research conducted with the communities of Arctic Bay and Igloolik in Nunavut identified key areas where policy can help Inuit reduce their vulnerability to climate change, focusing on the renewable resource harvesting sector. The policy responses are based on an understanding of policy development and decision making and on an understanding of the processes that shape vulnerability, which in Nunavut comprise the erosion of traditional Inuit knowledge and land-based skills, the weakening of social networks, and a reduction in harvesting flexibility. Policies relating to cultural preservation, wildlife comanagement, and harvester support can serve as entry points for influencing these processes. Our recommendations fall within the mandates of the Government of Nunavut and the institutions created under the Nunavut Land Claims Agreement, and they have been identified as policy priorities by communities and Inuit organizations. Grâce à des recherches effectuées auprès des collectivités de la baie de l’Arctique et d’Igloolik au Nunavut, on a réussi à déterminer comment la politique peut rendre les Inuits moins vulnérables au changement climatique en se concentrant sur le secteur de l’exploitation des ressources renouvelables. La compréhension de l’élaboration des politiques, de la prise de décisions et des processus qui engendrent la vulnérabilité permet d’aboutir à des réponses en vue de l’établissement de politiques. Au Nunavut, cette vulnérabilité se traduit par l’érosion des connaissances traditionnelles inuites et des habiletés d’utilisation de la terre, l’affaiblissement des réseaux sociaux et l’atténuation de la souplesse caractérisant l’exploitation. Les politiques en matière de conservation culturelle, de cogestion de la faune et de soutien à l’exploitation servent de point d’entrée pour influencer ces processus. Nos recommandations cadrent avec les mandats du gouvernement du Nunavut et des établissements créés en vertu de l’Entente de revendication territoriale du Nunavut. Les collectivités et organismes ...